Development of a global forearm reconstruction system for post-tumor resection defects of the radius or ulna: a proof-of-concept study - Liang, Haijie; Zang, Jie; Huang, Siyi; Wang, Boyang; Tang, Shun; Du, Zhiye; Qi, Feiyang; Guo, Wei; Wang, Jichuan; Tang, Xiaodong (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundBone defects resulting from sarcoma resection in the forearm present significant challenges for reconstruction, with limited guidance available in the literature.MethodsWe developed a novel series of 3D-printed endoprostheses, called the Global Forearm Reconstruction System (GFRS), to reconstruct defects of the proximal radius (PR), distal ulna (DU), total ulna (TU), and total radius (TR). Finite element analysis (FEA) was performed to determine the mechanical support function of the GFRS endoprostheses. We also tested the rotatory function of the endoprostheses ex vivo using a resin model. Finally, we summarized the preliminary outcomes of three pediatric cases using the GFRS endoprostheses for reconstruction.ResultsResection of PR, DU, TU and TR leads to stress concentration in the remaining structures, which can be mitigated by the corresponding GFRS endoprostheses. The novel endoprostheses demonstrated full supination capability and approximately 50% of pronation in the ex vivo model. All of the three clinical cases achieved satisfactory functional status (MSTS-93:28-29; MEPS: 95-100) without complications during mid-term follow-up (32–42 months).ConclusionIn this proof-of-concept study, we demonstrated that the GFRS endoprostheses not only meet the theoretical reconstruction requirements but also exhibit a good safety profile and produce satisfactory functional outcomes in a preliminary cohort with mid-term follow-up.